The role of heroic creativity and leadership in creative work - Bennett, Dawn; Efthimiou, Olivia; Allison, Scott (Edward Elgar Publishing, 2020)
This chapter explores the role of heroic creativity and heroic leadership in creative work. It does this by applying heroism theory to creative workers’ qualitative accounts of their careers. The chapter draws on creative workers’ responses to a creative industries survey implemented in Australia. Data were analysed for the presence of the three functions and nine underlying themes of heroic leadership. The findings suggest that heroic creativity and leadership feature strongly in the careers of creative workers. Awareness of both heroic creativity and leadership may be beneficial for equipping creative workers—and potentially other graduates and job seekers—with the resources to better negotiate the precarious 21st century labour market. The development of a heroic leadership profile may be an important attribute for optimising well-being, satisfaction, and the ability to cope with career challenges.